2014
DOI: 10.1108/ijopm-09-2012-0385
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SCOR’s approach to supply chain risk management

Abstract: Purpose – SCOR 10.0, released in late 2010, is the second version of the supply chain operations reference model (SCOR) to incorporate risk management processes, metrics and best practices. Given the paucity of studies that have explored the coverage and integration of supply chain risk management (SCRM) within SCOR, the analysis and suggested improvements for SCRM are designed to enhance SCOR’s collaborative and coordinated management of supply chain (SC) risks. The paper aims to dicsuss these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 70 publications
0
31
0
3
Order By: Relevance
“…The framework may also be extended to capture the dynamic behavior of risk over time. 2004Semi-quantitative Sinha et al (2004) * Kleindorfer and Saad (2005) Semi-quantitative Khan et al (2008) * Manuj and Mentzer (2008) x * Knemeyer et al (2009) x x Semi-quantitative Oehmen et al (2009) x x * Tuncel and Alpan (2010) x o Tummala and Schoenherr (2011) * Lavastre et al 2012x Semi-quantitative Elleuch et al (2014) x o Rotaru et al (2014) * Micheli et al (2014) x o Aqlan and Lam (2015) x o Giannakis and Papadopoulos (2016) x Semi-quantitative Qazi et al (2017) x x o of risks as shown in Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
“…The framework may also be extended to capture the dynamic behavior of risk over time. 2004Semi-quantitative Sinha et al (2004) * Kleindorfer and Saad (2005) Semi-quantitative Khan et al (2008) * Manuj and Mentzer (2008) x * Knemeyer et al (2009) x x Semi-quantitative Oehmen et al (2009) x x * Tuncel and Alpan (2010) x o Tummala and Schoenherr (2011) * Lavastre et al 2012x Semi-quantitative Elleuch et al (2014) x o Rotaru et al (2014) * Micheli et al (2014) x o Aqlan and Lam (2015) x o Giannakis and Papadopoulos (2016) x Semi-quantitative Qazi et al (2017) x x o of risks as shown in Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
“…The version 4 was the first to include return process in the supply chain. The Revisions of the model are made by the members of the Council when it is determined that modifications need to be made to facilitate the use of the model in practice [11]. The release of version 11 for access, as well as the incorporation of the new material into all SCOR ® training and certification programs, are announced by the Supply-Chain Council (SCC), the global not-forprofit organization supporting supply chain professionals and educators [12].…”
Section: Literature Review 21 the Supply Chain Operations Reference mentioning
confidence: 99%
“…The version 4 was the first to include return process in the supply chain. The Revisions of the model are made by the members of the Council when it is determined that modifications need to be made to facilitate the use of the model in practice [16]. The release of version 11 for access, as well as the incorporation of the new material into all SCOR ® training and certification programs, are announced by the Supply-Chain Council (SCC), the global not-for-profit organization supporting supply chain professionals and educators [17].…”
Section: The Supply Chain Operations Reference (Scor) Modelmentioning
confidence: 99%